Evaluation of PVA/Leucaena Leucocephala Blends Film for Antimicrobial Properties using Beef Meat Model - Annette Andrew H’ng (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To compare the effect of different PVA ratio incorporate with parts of.Leucaena Leucocephala such as leaves and seeds. To evaluate the antimicrobial activity efficiency of the film produced on the beef meat model. To characterize the properties of the best antimicrobial film produced by performing Fourier Transform Infrared (FTIR), tensile test and Scanning Electron Microscopy (SEM).